2013
DOI: 10.1371/journal.pone.0078507
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Insights into the Carbohydrate-Active Enzymes Carried by the Microorganisms Adhering to Solid Digesta in the Rumen of Cows

Abstract: The ruminal microbial community is a unique source of enzymes that underpin the conversion of cellulosic biomass. In this study, the microbial consortia adherent on solid digesta in the rumen of Jersey cattle were subjected to an activity-based metagenomic study to explore the genetic diversity of carbohydrolytic enzymes in Jersey cows, with a particular focus on cellulases and xylanases. Pyrosequencing and bioinformatic analyses of 120 carbohydrate-active fosmids identified genes encoding 575 putative Carbohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
74
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 37 publications
11
74
0
3
Order By: Relevance
“…More recently, metagenomic studies have revealed enzymes from uncultured and deeply branched lineages, which constitute the majority of microorganisms within rumen microbiomes (15). While PULs originating from uncultured rumen bacteria have previously been detected (12,14,33,34), here we have taken additional measures to partially describe the enzymatic capabilities of one such PUL encoded within a numerically abundant uncultured phylotype. The GH5_g -GH5_h…”
Section: Resultsmentioning
confidence: 96%
“…More recently, metagenomic studies have revealed enzymes from uncultured and deeply branched lineages, which constitute the majority of microorganisms within rumen microbiomes (15). While PULs originating from uncultured rumen bacteria have previously been detected (12,14,33,34), here we have taken additional measures to partially describe the enzymatic capabilities of one such PUL encoded within a numerically abundant uncultured phylotype. The GH5_g -GH5_h…”
Section: Resultsmentioning
confidence: 96%
“…1) through (meta)genomic, transcriptomic, and proteomic approaches (93)(94)(95)(96). PULs have been identified in species outside the Bacteroides genus in diverse environments, including the ruminal Prevotella bryantii (97), the freshwater dweller Flavobacterium johnsoniae (98), and the gut microbiota of the termite Pseudacanthotermes militaris (99).…”
Section: Pulomicsmentioning
confidence: 99%
“…To bypass the cultivation step, metagenomic approaches involving the direct analysis of total DNA sequences have been extensively used to investigate the PCWP-degrading gastrointestinal microbes in a variety of herbivores, such as termite hindguts (5); cow (6)(7)(8), yak (9), and Svalbard reindeer (10) rumens; and the foreguts of Australian macropods (11). It has been demonstrated that PCWP-degrading enzymes that exist in the rumen are far more diverse than was previously believed.…”
mentioning
confidence: 99%